PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI INVENTORY BERBASIS WEBSITE MENGGUNAKAN ITERATIVE WATERFALL - Michael Lowman Stinjak; Fajar Masya (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
As a provider company, warehousing management is very important for PT Dolok Mitra Sinergi, especially in the procurement process, such as by checking in the warehouse in real time so as to create company effectiveness and efficiency. PT DOLOK MITRA SINERGI has a warehouse where the warehouse is still implementing data collection using Excel, coordination errors and communication between related units, so that there are many errors found in the inventory data collection process and also the amount of time used in the data collection process. Based on the problems found in the company's warehouse, the authors propose a website-based information system that can manage inventory in the company. In the application design process, the Iterative Waterfall methodology is used in compiling the flow. With this Inventory Application, it is hoped that it can help PT Dolok Mitra Sinergi to handle problems that exist in warehousing activities.